Standards And Practice in Management of Medical Device - Ngoie, Jean (CMBES Proceedings, 2006)
The purpose of this paper is to raise awareness within the Biomedical and Clinical engineering community, about the issue of understanding the standards. Also, open a discussion about current practices in management of medical devices in general and laboratory equipment in particular. The paper focuses on similarities between medical electrical equipment and medical electrical laboratory equipment standards. The influence of these standards on today’s technologically advanced healthcare. The paper looks at risks associates with current laboratory equipment management practices. A common practice is suggested as the next step forward. The paper also highlights some benefits of a common practice in the management of medical and laboratory equipment.